Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Given the equation:
[tex]\[ \frac{x}{x-1} + \frac{4}{x} = 4, \][/tex]
we need to find the solutions for \( x \).
Let's start solving the equation step by step:
### Step 1: Eliminate the fractions.
The equation contains fractions, so the first step is to eliminate them by finding a common denominator. The denominators here are \( x \) and \( x - 1 \), so the common denominator is \( x(x - 1) \).
Multiply every term by this common denominator:
[tex]\[ x(x - 1) \left( \frac{x}{x-1} \right) + x(x-1) \left( \frac{4}{x} \right) = 4 x(x-1) \][/tex]
### Step 2: Simplify the equation.
Simplify each term:
[tex]\[ x^2 + 4(x-1) = 4x(x - 1) \][/tex]
Distribute the terms:
[tex]\[ x^2 + 4x - 4 = 4x^2 - 4x \][/tex]
### Step 3: Move all terms to one side of the equation.
Bring all terms to one side such that the equation equals zero:
[tex]\[ x^2 + 4x - 4 - 4x^2 + 4x = 0 \][/tex]
Combine like terms:
[tex]\[ -x^2 + 8x - 4 = 0 \][/tex]
This can be written as:
[tex]\[ -x^2 + 8x - 4 = 0 \][/tex]
or multiplying by -1 to simplify:
[tex]\[ x^2 - 8x + 4 = 0 \][/tex]
### Step 4: Solve the quadratic equation.
This is a standard quadratic equation of the form \( ax^2 + bx + c = 0 \). We can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, \( a = 1 \), \( b = -8 \), and \( c = 4 \). Substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4(1)(4)}}{2(1)} \][/tex]
Simplify inside the square root:
[tex]\[ x = \frac{8 \pm \sqrt{64 - 16}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{48}}{2} \][/tex]
Simplify the square root:
[tex]\[ x = \frac{8 \pm 4\sqrt{3}}{2} \][/tex]
[tex]\[ x = 4 \pm 2\sqrt{3} \][/tex]
### Step 5: Convert approximate values.
We know that \( \sqrt{3} \approx 1.732 \):
So,
[tex]\[ x \approx 4 \pm 2 \cdot 1.732 \][/tex]
[tex]\[ x \approx 4 \pm 3.464 \][/tex]
This gives us two solutions:
[tex]\[ x \approx 4 + 3.464 \approx 7.464 \][/tex]
[tex]\[ x \approx 4 - 3.464 \approx 0.536 \][/tex]
For the given choices:
### Comparison:
The numerical solutions closest to the calculated values (converted to exact forms) would be:
[tex]\[ x \approx \frac{2}{3} \approx 0.667 \][/tex]
and
[tex]\[ x = 2 \][/tex]
Thus, the correct answer is:
b) [tex]\( \frac{2}{3}, 2 \)[/tex]
[tex]\[ \frac{x}{x-1} + \frac{4}{x} = 4, \][/tex]
we need to find the solutions for \( x \).
Let's start solving the equation step by step:
### Step 1: Eliminate the fractions.
The equation contains fractions, so the first step is to eliminate them by finding a common denominator. The denominators here are \( x \) and \( x - 1 \), so the common denominator is \( x(x - 1) \).
Multiply every term by this common denominator:
[tex]\[ x(x - 1) \left( \frac{x}{x-1} \right) + x(x-1) \left( \frac{4}{x} \right) = 4 x(x-1) \][/tex]
### Step 2: Simplify the equation.
Simplify each term:
[tex]\[ x^2 + 4(x-1) = 4x(x - 1) \][/tex]
Distribute the terms:
[tex]\[ x^2 + 4x - 4 = 4x^2 - 4x \][/tex]
### Step 3: Move all terms to one side of the equation.
Bring all terms to one side such that the equation equals zero:
[tex]\[ x^2 + 4x - 4 - 4x^2 + 4x = 0 \][/tex]
Combine like terms:
[tex]\[ -x^2 + 8x - 4 = 0 \][/tex]
This can be written as:
[tex]\[ -x^2 + 8x - 4 = 0 \][/tex]
or multiplying by -1 to simplify:
[tex]\[ x^2 - 8x + 4 = 0 \][/tex]
### Step 4: Solve the quadratic equation.
This is a standard quadratic equation of the form \( ax^2 + bx + c = 0 \). We can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, \( a = 1 \), \( b = -8 \), and \( c = 4 \). Substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4(1)(4)}}{2(1)} \][/tex]
Simplify inside the square root:
[tex]\[ x = \frac{8 \pm \sqrt{64 - 16}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{48}}{2} \][/tex]
Simplify the square root:
[tex]\[ x = \frac{8 \pm 4\sqrt{3}}{2} \][/tex]
[tex]\[ x = 4 \pm 2\sqrt{3} \][/tex]
### Step 5: Convert approximate values.
We know that \( \sqrt{3} \approx 1.732 \):
So,
[tex]\[ x \approx 4 \pm 2 \cdot 1.732 \][/tex]
[tex]\[ x \approx 4 \pm 3.464 \][/tex]
This gives us two solutions:
[tex]\[ x \approx 4 + 3.464 \approx 7.464 \][/tex]
[tex]\[ x \approx 4 - 3.464 \approx 0.536 \][/tex]
For the given choices:
### Comparison:
The numerical solutions closest to the calculated values (converted to exact forms) would be:
[tex]\[ x \approx \frac{2}{3} \approx 0.667 \][/tex]
and
[tex]\[ x = 2 \][/tex]
Thus, the correct answer is:
b) [tex]\( \frac{2}{3}, 2 \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.